Identity and phylogenetic placement of Spirogyra species (Zygnematophyceae, Charophyta) from California streams and elsewhere1. Issue 3 (10th May 2013) - Stancheva, Rosalina; Hall, John D.; McCourt, Richard M.; Sheath, Robert G.; Gabrielson, P.
<x xml:space="preserve">Abstract</x> Diversity of the filamentous green algae in the genus Spirogyra (Zygnematophyceae) was investigated from more than 1, 200 stream samples from California. We identified 12 species of Spirogyra not previously known for California (CA), including two species new to science, Spirogyra californica sp. nov. and Spirogyra juliana sp. nov. Environmental preferences of the Californian species are discussed in the light of their restricted distribution to stream habitats with contrasting nutrient levels. We also investigated the systematic relationships of Spirogyra species from several continents using the chloroplast‐encoded genes ribulose‐1, 5‐bisphosphate carboxylase/hydrogenase large subunit (rbcL) and the beta subunit of the ATP synthase (atpB). Californian species were positioned in most major clades of Spirogyra. The phylogeny of Spirogyra and its taxonomic implications are discussed, such as the benefits of combining structural and molecular data for more accurate and consistent species identification. Considerable infraspecific genetic variation of globally distributed Spirogyra species was observed across continental scales. This finding suggests that structurally similar species from distant regions may be genetically dissimilar and that Spirogyra may contain a large number of cryptic species. Correlating the morphological and genetic variation within the genus will be a major challenge for future researchers.